STUDY OF PRESCRIPTION PROFILE OF PATIENTS WITH BRONCHIAL ASTHMA AT PARSOBURAN COMMUNITY HEALTH CITY PEMATANGSIANTAR PERIOD JANUARY-MARCH 2017 - Yulia Delfahedah; Arsiaty (PT. Radja Intercontinental Publishing, 2020)
Bronchial asthma has varying incidence rates in different countries, but there is a tendency for this disease to increase in number, even though asthma medications have been developed. This study aims to determine the pattern of treatment of bronchial asthma in patients at the Parsoburan Health Center, Pematangsiantar City for the period January-March 2017. This research was a non-experimental (observational) descriptive study conducted using a retrospective method. The data used are medical records of bronchial asthma patients. The results of the study showed that in the January-March 2017 period there were 18 cases of bronchial asthma. The gender distribution of bronchial asthma patients was 66.7% male and 33.3% female, while the age distribution of bronchial asthma patients was divided into 4 groups, namely, Toddlers (0≤5 years) by 33.3%, children (5<n<12 years) by 5.6%, adults (12<n<65 years) by 38.9%, and elderly (> 65 years) of 22.2% The general description of prescribing the highest number of drugs given to bronchial asthma patients in one prescription are 5 and 6 drugs each of 38.9%, the distribution of drug classes used for therapy includes, bronchodilators 25, 7%, mucolytic 18.5%, corticosteroid 15.5%, anti-microbial 15.5%, anti-hypoxemia 4.1%, analgesic 6.2%, anti-histamine 3.1% and accompanying drugs (anti- diabetic, anti-epileptic, anti-hypertensive, anti-angina, and vitamins) given at 1% each. Distribution of discrepancies in drug administration based on the Indonesian National Drug Informatorium standard of 17.5%, based on the Physicians Drug Handbook standard of 0%,